The Analysis of Diversification in China---- The Motivations for Diversification of Chinese Organisations - Qiao, Zhenyu (2005)
China, as a developing country, has become the focus of attention because of its recent strong and quick economic development. Studies aimed to understand Chinese organisations' behaviour is deemed important. Diversification, as core part of corporate strategy, is an important subject in these studies.